2015
DOI: 10.1007/s13246-015-0363-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel ultrasound based approach for lesion segmentation and its applications in gynecological laparoscopic surgery

Abstract: Laparoscopic ultrasound (LUS) has been widely utilized as a surgical aide in general, urological, and gynecological applications. Our study summarizes the clinical applications of laparoscopic ultrasonography in laparoscopic gynecologic surgery. Retrospective analyses were performed on 42 women subjects using laparoscopic surgery during laparoscopic extirpation and excision of gynecological tumors in our hospital from August 2011 to August 2013. Specifically, the Esaote 7.5 × 10 MHz laparoscopic transducer was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, the study did not identify improvement in diagnostic accuracy for borderline or malignant lesions as there were too few of these cases to achieve statistical power [67]. Gong et al found LUS to be very beneficial in lesion segmentation in benign gynecology cases, highlighting the major benefit to be image representation beyond tissues boundaries [68]. However, while the 42 women in the study were benign, the obvious potential to extrapolate into the gynecological oncology setting is clear, although further evidence is needed.…”
Section: Laparoscopic Us In Gynecological Oncologymentioning
confidence: 92%
“…However, the study did not identify improvement in diagnostic accuracy for borderline or malignant lesions as there were too few of these cases to achieve statistical power [67]. Gong et al found LUS to be very beneficial in lesion segmentation in benign gynecology cases, highlighting the major benefit to be image representation beyond tissues boundaries [68]. However, while the 42 women in the study were benign, the obvious potential to extrapolate into the gynecological oncology setting is clear, although further evidence is needed.…”
Section: Laparoscopic Us In Gynecological Oncologymentioning
confidence: 92%